Experimental study on phase equilibria of CaO–Al2O3–CeO2 system at 1673∼1873K - Guojie Huo; Jiyu Qiu; Chengjun Liu (Journal of Materials Research and Technology)
CaO–Al2O3–CeO2 system is a basic slag system for pyrometallurgical comprehensive utilization of various rare earth (RE) containing slag/tailings resources. The phase diagram of this system is useful for the research and development of related processes; besides, it is also indispensable for the thermodynamic database of multicomponent rare earth (RE) containing slag systems. In this paper, we employed high-temperature equilibrium experiments and quenching methods followed by scanning electron microscope (SEM), electron probe microanalysis (EPMA) and X-ray diffraction (XRD) to determine the morphology, composition and type of equilibrium phases in the CaO–Al2O3–CeO2 system, respectively. Combining the current work and literature data, three isothermal sections at 1873K (including 2 three-phase fields, 3 two-phase fields and a liquid phase field), at 1773K (including 4 three-phase fields, 4 two-phase fields and a liquid phase field) and at 1673K (including 4 three-phase fields, 3 two-phase fields and a liquid phase field) were clarified. The liquidus projection of the CaO–Al2O3–CeO2 system with primary phase fields and Alkemade lines was obtained. Subsequently, the types and possible temperature ranges of 6 univariant reactions and 3 invariant reactions were discussed, respectively.